Carbon and chlorine isotopologue fractionation of chlorinated hydrocarbons during diffusion in water and low permeability sediments. (15th May 2015) - Wanner, Philipp; Hunkeler, Daniel
Abstract: To identify reactive processes in diffusion dominated water-saturated systems using compound-specific isotope analysis (CSIA), the effect of the diffusive transport process on isotope ratios needs to be known. This study aims to quantify the magnitude of carbon and chlorine isotopologue fractionation of two chlorinated hydrocarbons (trichloroethene (TCE) and 1, 2-dichloroethane (1, 2-DCA)) during diffusion in the aqueous phase and to relate for the first time laboratory with field results. Diffusion coefficient ratios in the aqueous phase were experimentally quantified with a modified Stokes diffusion cell. The experiment revealed a significant shift of carbon and chlorine isotopologue ratios of TCE and 1, 2-DCA during diffusion. For both TCE and 1, 2-DCA, the magnitude of the shift of chlorine isotopologue ratios was larger (TCE: D132 /D130 = 0.99963 ± 0.00003; 1, 2-DCA: D102 /D100 = 0.99939 ± 0.00003) in comparison to carbon isotopologue ratios (TCE: D131 /D130 = 0.99978 ± 0.00006; 1, 2-DCA: D101 /D100 = 0.99977 ± 0.00004), which is consistent with the larger mass difference between stable chlorine compared to carbon isotopes. Determined diffusion coefficients for carbon and chlorine isotopologues of TCE and 1, 2-DCA follow an inverse power law form ( D ∝ m - β ) with β < 0.5 revealing that the magnitude of isotopologue fractionation of TCE and 1, 2-DCA is lower than in the previously postulated kinetic theory ( D ∝ m - 0.5 ). To relate laboratory with field results, a water-saturated clay core from a VOC contaminated site was retrieved and subsampled as a function of depth to assess possible shifts in isotopologue ratios during downward diffusion of VOCs into the low permeable clay. Observed small shifts of TCE carbon and chlorine isotopologue ratio profiles were consistent with laboratory determined diffusion coefficient ratios, demonstrated by a 1D-diffusion model. Further 1D-simulations for shorter diffusion periods (5–10 years) than observed in the retrieved clay core (45 years), revealed a larger effect on TCE chlorine and carbon isotopologue ratio profiles. Thus, the diffusive transport process in water-saturated low permeability sediments only impairs the identification of reactive processes using compound-specific isotope analysis (CSIA) during short diffusion periods and for reactive processes with small enrichment factors.